Deaths from HIV/AIDS in aged adults in the Federal District: an analysis from 2007 to 2016 - Sacco, Ruth da Conceição Costa e Silva; Magalhães, Raissa Gomes; Cabral, Amanda de Siqueira; Escalda, Patrícia Maria Fonseca (Brazilian Journal of Sexually Transmitted Diseases, 2020)
Introduction: Infection with the human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS) in Brazil experienced a significant increase in the last decade among individuals aged over 60 years. This scenario indicates the need to know the mortality profile from AIDS in aged adults, in order to promote educational and preventive actions, in addition to professional development to improve the care provided to these patients. Objective: To describe the epidemiological profile of aged adults who died of AIDS in the Federal District (FD) from 2007 to 2016. Methods: This is a descriptive ecological study, based on secondary data from the Brazilian Mortality Information System, obtained through the Health Situation Analysis and Data Management of the Health Department of the FD. The analysis was carried out in the Statistical Package for the Social Sciences (SPSS). Results: Deaths occurred more frequently among men (74.1%), especially those aged from 60 to 69 years (70.4%). The gender ratio was 2.85. Most of them only had primary school education (42.0%), were married or in a common-law marriage (43.0%), and were white/Caucasian (52%). Regarding the place of residence, Plano Piloto was the place with the highest incidence (45.7%), followed by Ceilândia (12.3%) and Taguatinga (8.6%). Conclusion: It was found that AIDS, among aged adults, follows the national trend, occurring most frequently in older males, demonstrating that it is necessary to improve the implementation of prevention practices among this population. It is necessary to better study AIDS-related stigma and prejudice barriers, both among older adults and health professionals, to overcome them, to increase life expectancy of these patients and to improve their quality of life.